Systemic immune‐inflammation index (SII) is useful to predict survival outcomes in patients with surgically resected non‐small cell lung cancer. Issue 4 (7th February 2019) - Guo, Wei; Cai, Songhua; Zhang, Fan; Shao, Fei; Zhang, Guochao; Zhou, Yang; Zhao, Liang; Tan, Fengwei; Gao, Shugeng; He, Jie
Abstract : Background: The systemic immune‐inflammation index (SII) is correlated with patient survival in various types of solid tumors. However, only a few studies have focused on the prognostic value of the SII in patients with surgically resected non‐small cell lung cancer (NSCLC). Methods: This study was a single center retrospective analysis of 569 NSCLC patients who underwent curative lobectomy at the Department of Thoracic Surgery, National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College between 2006 and 2012. A receiver operating characteristic curve was plotted to compare the discriminatory ability of the SII for overall survival (OS). A Cox proportional hazards regression model was used to perform univariate and multivariate analyses. Results: The SII, neutrophil‐lymphocyte ratio (NLR), and platelet‐lymphocyte ratio (PLR) all correlated with OS in NSCLC patients, and the SII was an independent prognostic factor for OS (hazard ratio 1.256, 95% confidence interval 1.018–1.551; P = 0.034). The area under the receiver operating characteristic curve of the SII (0.547) was larger than the NLR (0.541) and PLR (0.531). Furthermore, the SII retained prognostic significance in the lung adenocarcinoma subgroup. Conclusion: The SII is a promising prognostic predictor for patients with surgically resected NSCLC and retained prognostic significance in the lung adenocarcinoma subgroup. The prognostic value of the SII is superior to the NLR and PLR.